2017
DOI: 10.1177/0091450917694268
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Effects, Health Service Engagement, and Service Satisfaction Among Anabolic Androgenic Steroid Users

Abstract: There are a number of adverse health effects associated with the use of anabolic androgenic steroids (AAS) ranging from mood disturbances to gynaecomastia and impaired sexual function. Despite the potentially serious nature of adverse effects, evidence suggests that users are reluctant to seek medical assistance. This study explores factors associated with health service engagement and treatments related to service satisfaction among a sample of AAS users. The analyses are based on a sample of 195 respondents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(85 citation statements)
references
References 49 publications
2
80
3
Order By: Relevance
“…In countries such as the UK and Australia needle and syringe programmes are a common source of injecting equipment (Dunn, Henshaw, & McKay, 2016;Kimergård & McVeigh, 2014b) and with AAS associated with a range of acute and chronic adverse effects (including those associated with needle sharing) healthcare is important. However many users may be reluctant to engage with healthcare services (Zahnow, McVeigh, Ferris, & Winstock, 2017) and report concerns about stigma, knowledge and attitudes of health professionals that may reduce contact (Dunn et al, 2016). Men with strong masculine values may be reluctant to engage with the health care system (Courtenay, 2000;Springer & Mouzon, 2011).…”
Section: Community Levelmentioning
confidence: 99%
“…In countries such as the UK and Australia needle and syringe programmes are a common source of injecting equipment (Dunn, Henshaw, & McKay, 2016;Kimergård & McVeigh, 2014b) and with AAS associated with a range of acute and chronic adverse effects (including those associated with needle sharing) healthcare is important. However many users may be reluctant to engage with healthcare services (Zahnow, McVeigh, Ferris, & Winstock, 2017) and report concerns about stigma, knowledge and attitudes of health professionals that may reduce contact (Dunn et al, 2016). Men with strong masculine values may be reluctant to engage with the health care system (Courtenay, 2000;Springer & Mouzon, 2011).…”
Section: Community Levelmentioning
confidence: 99%
“…It is noteworthy that people who use AAS will experience these risks to different degrees, and many take time to research the different substances (Christiansen, Vinther, and Liokaftos 2016) and mitigate for side effects. Moreover, people take different approaches to risk management, e.g., one study found only 22% of AAS users accessed BBV tests (Hope et al 2015) despite the risks and another found that 67% of AAS users did not visit a doctor despite being worried about the negative side effects, as they did not think it serious enough (Zahnow et al 2017).…”
Section: Harms Associated With Using Aasmentioning
confidence: 99%
“…In one study, a participant explained that his doctor had no time for him, and expressed his frustration that the doctor would have done had he been seeking help for the consequences of smoking or drinking (Walker and Eli Joubert 2011). This distrust of medical professionals by people who use AAS is found across a large range of studies (Grogan et al 2006;Zahnow et al 2017;Cohen et al 2007;Maycock and Howat 2005). The implication being that carrying out activities that cause harm, but are socially acceptable and possibly engaged in by the professional themselves, allows access to services.…”
Section: The Legal Situationmentioning
confidence: 99%
“…The main reason is likely that very few countries have implemented treatment of AAS-related health problems in the SUD treatment system. It is important to note that few users seek any health services (Pope, Khalsa, and Bhasin 2017;Zahnow et al 2017), despite being concerned for their health (Zahnow et al 2017). Barriers include fear of stigmatization (Dunn, Henshaw and Mc Kay 2016;Yu, Hildebrandt, and Lanzieri 2015), unknowledgeable staff (Jørstad, Skogheim, and Bergsund 2018;Pope et al 2004), sanctions (Havnes, Jørstad and Wisløff 2019), belief that the treatment provider cannot/will not help, or belief that the health problem is not serious enough (Zahnow et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that few users seek any health services (Pope, Khalsa, and Bhasin 2017;Zahnow et al 2017), despite being concerned for their health (Zahnow et al 2017). Barriers include fear of stigmatization (Dunn, Henshaw and Mc Kay 2016;Yu, Hildebrandt, and Lanzieri 2015), unknowledgeable staff (Jørstad, Skogheim, and Bergsund 2018;Pope et al 2004), sanctions (Havnes, Jørstad and Wisløff 2019), belief that the treatment provider cannot/will not help, or belief that the health problem is not serious enough (Zahnow et al 2017). Yet, among a sample of Norwegian AAS users where mental health problems were the most common motivation for AAS cessation and treatment seeking, three out of four desired SUD treatment after receiving information tailored to AAS users about side effects, treatment options and potential outcomes (Havnes, Jørstad and Wisløff).…”
Section: Introductionmentioning
confidence: 99%